Parochial education in a global world? Teaching history and civics in Lebanon - Bahous, Rima (2013)
This exploratory article is based on a researchproject which runs 2011-2013 that examines how global processes are expressedin educational policies and pedagogical texts in Lebanon, Sweden and Turkey byfocusing on school subjects like civics, history, geography, and religion. In thistext we discuss the development ofeducation in Lebanon, the development of history and civics after the civilwar, and on opinions about these school subjects in order to make a preliminaryanalysis of how the future Lebanese citizen is depicted in policies,curricula, and textbooks. Lebanon is interesting because of its uniqueeducation system in which foreign international institutions rather thannational ones have the task of preparing individuals for a globalized world.Material for the study were collected from a sample of curricula used inprivate and public or national schools for history and civics/citizenshipeducation in grade 8 as well as interviews and conference proceedings andconversations with activists, teachers and principals. We also reviewedfindings of relevant empirical studies conducted in Lebanon. Our datacollection was guided by three questions: how is the right citizen depicted inthe Lebanese material? How is the relationship between national and globalperspectives treated in guidance documents and pedagogical texts? What civicrights and obligations are given attention and what individuals are included/excluded? Our preliminary findings imply that there is no consensus on theimportance of teaching a unified history and civics book and subjects inLebanon. Other findings indicate that private and international schools have agreater impact than national schools on preparing Lebanese students as futurecitizens.